Fitting social enterprise for sustainable development in Vietnam - Nguyen MHT; Hodgetts DJ; Carr SC (MDPI (Basel, Switzerland), 2021)
Drawing on aspects of both commercial and not-for-profit organisational structures, social enterprises strive to become financially sustainable in order to support efforts to address various societal problems, including poverty and socio-economic exclusions. This study documents the experiences of 20 social entrepreneurs regarding the fit between their leadership practices, social enterprises and the Vietnamese societal ecosystem. Results from semi-structured go-along interviews foreground the importance of fit between the societal eco-system, key cultural values and relational practices, entrepreneur leadership and the structure and functioning of social enterprises in achieving their pro-social missions. This article contributes to emerging literature on the sustainability of social enterprises in emerging economies and is currently being drawn upon in the development of policy responses in Vietnam.
Keywords: social entrepreneurship; person-environment fit; leadership; pro-social impacts; culture